2021
DOI: 10.7861/clinmed.2020-0962
|View full text |Cite|
|
Sign up to set email alerts
|

Developing services for long COVID: lessons from a study of wounded healers

Abstract: Persistent symptoms lasting longer than 3 weeks are thought to affect 10-2 0% of patients following SARS-CoV-2 infection. No formal guidelines exist in the UK for treating patients with long COVID and services are sporadic and variable, although additional funding is promised for their development.In this study, narrative interviews and focus groups are used to explore the lived experience of 43 healthcare professionals with long COVID. These individuals see the healthcare system from both professional and pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 14 publications
5
113
0
4
Order By: Relevance
“…It would appear that long COVID has so far avoided the earlier obscure fate of ME/CFS, with an outpouring of public and expert acknowledgement for its status as a medical illness and its significant long-term health impact [79][80][81][82]. Many have attested to the importance of providing patient support and monitoring patients' chronic symptoms post-COVID, as well as the need for further research into long COVID [83][84][85]. Though there is no established treatment protocol for patients with long COVID symptoms, many have acknowledged and suggested the need and benefits of rehabilitation [86,87].…”
Section: Discussionmentioning
confidence: 99%
“…It would appear that long COVID has so far avoided the earlier obscure fate of ME/CFS, with an outpouring of public and expert acknowledgement for its status as a medical illness and its significant long-term health impact [79][80][81][82]. Many have attested to the importance of providing patient support and monitoring patients' chronic symptoms post-COVID, as well as the need for further research into long COVID [83][84][85]. Though there is no established treatment protocol for patients with long COVID symptoms, many have acknowledged and suggested the need and benefits of rehabilitation [86,87].…”
Section: Discussionmentioning
confidence: 99%
“… 9 Enabling self-management in the community is a key arm in the multidisciplinary approach to the management of long COVID. 10 This can include education regarding self-monitoring, patient support groups, and direction regarding management of mental health. This could perhaps be undertaken by trained non-clinical staff such as social prescribers in the first instance, providing welfare calls with a clinician’s review where indicated.…”
Section: Discussionmentioning
confidence: 99%
“…While exercise is likely to be beneficial for some, there are many unknowns, including whether all patients with persistent symptoms should undergo screening for respiratory and cardiac complications before beginning exercise; whether exercise rehabilitation needs to be medically supervised; what level of tailoring is required; what frequency, intensity, duration and type of exercise can be recommended; and the trajectory of recovery for people living with long COVID. These uncertainties, and the fact that little data exists to date, mean treatment may require a multidisciplinary care pathway [87,88]. Limited reporting of interventions with overinterpretations regarding safety [21] do not serve the long COVID research, allied health professional, nor patient community.…”
Section: Discussionmentioning
confidence: 99%